2018
DOI: 10.1017/s000711451700397x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D intake, serum 25-hydroxyvitamin D status and response to moderate vitamin D3supplementation: a randomised controlled trial in East African and Finnish women

Abstract: Insufficient vitamin D status (serum 25-hydroxyvitamin D (S-25(OH)D)0·05 for differences between ethnic groups). In conclusion, high prevalence of vitamin D insufficiency existed among East African women living in Finland, despite higher vitamin D intake than their Finnish peers. Moderate vitamin D3 supplementation was effective in increasing S-25(OH)D in both groups of women, and no ethnic differences existed in the response to supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 47 publications
4
24
0
Order By: Relevance
“…One of our core commitments in the ODIN project was to address under-represented groups among the healthy population for whom data to base estimates for vitamin D recommendations were scarce or absent [ 5 , 6 , 7 , 8 , 9 , 10 ]; namely young children, adolescents, pregnant women and persons of ethnic minority. Thus, four 25(OH)D-vitamin D 3 dose-response RCTs were designed and implemented to estimate the dietary requirements for vitamin D to meet 25(OH)D targets of 25/30 to 50 nmol/L in most (97.5%) individuals in these subgroups, under conditions of absent or scarce UVB exposure, providing evidence on which to base dietary allowances for them [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of our core commitments in the ODIN project was to address under-represented groups among the healthy population for whom data to base estimates for vitamin D recommendations were scarce or absent [ 5 , 6 , 7 , 8 , 9 , 10 ]; namely young children, adolescents, pregnant women and persons of ethnic minority. Thus, four 25(OH)D-vitamin D 3 dose-response RCTs were designed and implemented to estimate the dietary requirements for vitamin D to meet 25(OH)D targets of 25/30 to 50 nmol/L in most (97.5%) individuals in these subgroups, under conditions of absent or scarce UVB exposure, providing evidence on which to base dietary allowances for them [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a third ODIN dose-response RCT with a similar design to those in children and adolescents, vitamin D requirements of 69 women of Finnish descent were compared with 47 East African women in Helsinki (60° N), during wintertime [ 24 , 25 ]. By way of context for this RCT, Finland has a mandatory fortification programme of fluid milk products and spreads and there is a high level of awareness of vitamin D nutrition and health among Finnish residents of all nationalities [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reporting vitamin D status in different ethnic minority populations are presented in Table 1 [10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. The study of Black et al [12] reported vitamin D status in the West Australian Pregnancy Cohort, which showed the vitamin D status of Caucasians to be significantly higher than non-Caucasians ( p < 0.001).…”
Section: Vitamin D Status and Vitamin D Intake Of Ethnic Minority mentioning
confidence: 99%
“…The study of Hypponen and Power [27] showed that the prevalence of hypovitaminosis D in the UK was especially high in the winter and spring seasons [27]. There are a few studies [10,20,21,23] which reported vitamin D status in different ethnicities in winter. For example Nerhus et al [20] reported that the ethnic minority population had significantly lower serum 25(OH)D concentrations (mean 29.5 nmol/L, SD = 16.3) in winter than participants from the majority of the population (mean 50.4 nmol/L, SD = 19.1) in Norway, although serum 25(OH)D of different ethnic minorities was not investigated separately.…”
Section: Vitamin D Status and Vitamin D Intake Of Ethnic Minority mentioning
confidence: 99%